Business Model Canvas Analysis in Developing Business Strategies at Win Production Wedding Organizer in Bandar Lampung City, Indonesia - Suci Asfarani; Niki Agus Santoso (Sanskara Ekonomi dan Kewirausahaan, 2026)
This research aims to analyze the Business Model Canvas (BMC) as a business strategy for Win Production Wedding Organizer in Bandar Lampung City. The increasing competition in the wedding organizer industry demands that business actors have a structured, adaptive, and sustainable business strategy. The Business Model Canvas approach is used to map the business model evenly through nine main elements: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. This research uses a qualitative method with a descriptive approach. Information collection methods are attempted through in-depth interviews, direct observation, and documentation. Research informants consist of the owner, employees, and customers of Win Production Wedding Organizer. The validity of the information is tested using source triangulation and method triangulation. The results show that Win Production's main customer segment is bridesmaids from the middle to upper middle class who require reliable and instant wedding services. The main value offered is integrated, flexible, and hands-on wedding services tailored to client needs. The use of social media as the main marketing channel and personal relationships with customers are aspects that support business competitiveness. All elements of the Business Model Canvas are integrated and contribute to increasing the effectiveness of business strategies and business aspirations.